Molecular characterization of an outbreak of respiratory syncytial virus (subgroup A) in Havana, Cuba, by monoclonal antibodies and restriction mapping (N gene). - Valdivia, A (1997)
Twenty-one respiratory syncytial virus (RSV) strains isolated from one outbreak in Havana, Cuba (1994 to 1995), were analyzed to determine their relatedness. All isolated strains were classified as subgroup A by monoclonal antibodies. Of 21 RSV strains examined, 20 were classified as having restriction pattern NP4 and only 1 was classified as having restriction pattern NP5.